Associated anomalies in cleft lip and palate: Analysis of 811 consecutive patients - Adesina O A; Efunkoya A A; Olaitan A; Adesina O O (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2017)
Introduction: Clefts are common birth defects and may be associated with oro-facial congenital anomalies. It has not been established if specific types of anomalies are frequently related with clefts, or which organ is most commonly affected. This study aimed to assess the prevalence of associated anomalies in consecutive cleft lip and palate patients treated at two referral centres in Northern Nigeria. Methods: Cleft lip and palate at two referral hospitals in Northern Nigeria from January 2012 to December 2015 were studied. Data were analysed using Statistical Package for Social Sciences (SPSS) version 16. Results: A total of 811 cleft lip and palate patients were managed. Fifty-five percent (447) were male and 45% (364) were female while 71% (578) were children and 29% (233) were adults. The prevalence of associated anomalies was 11.5%. The most common associated anomaly among cleft patients was facial anomaly (64% of cleft patients). Associated anomalies were most prevalent in patients with isolated cleft palate. Hypertelorism was the commonest type of facial anomaly recorded. Conclusion: Our study showed a low incidence of associated anomalies with a higher incidence in isolated cleft palate cases.